Pathogenicity testing and antimicrobial susceptibility of Helicobacter pullorum isolates from chicken origin - A.K. Hassan (International Journal of Veterinary Science and Medicine, 2014)
This work aimed to study the pathogenicity and to investigate the antimicrobial susceptibility and resistance patterns of Helicobacter pullorum (H. pullorum). The minimum inhibitory concentration (MIC) value of ciprofloxacin, ampicillin, gentamycin, erythromycin, colistin sulfate and tetracycline was determined for eight different H. pullorum isolates. H. pullorum resulted into 33.3% mortality of infected chickens with signs of diarrhea, stunted growth and poor conversion rate in survivors. All experimentally infected embryonated chicken eggs showed embryonic mortalities within 48-h post yolk sac inoculation. H. pullorum was re-isolated from cecum, liver, yolk sac and air-sacs of all dead and sacrificed infected chickens. H. pullorum was also re-isolated from dead embryos, embryonic membranes and fluids of infected embryonated chicken eggs. Polymerase Chain Reaction (PCR) assay was used to detect H. pullorum in experimentally infected chickens and embryonated chicken eggs. All tested H. pullorum isolates were resistant to ciprofloxacin, gentamycin and erythromycin, while 7 out of 8 isolates were resistant to tetracycline. All isolates were susceptible to colistin sulfate and ampicillin.